Sensitivity evaluation of SYBR green I, SYBR safe and calcein dyes for detection of human papillomavirus 16 by loop-mediated isothermal amplification - Suharni Mohamad; Nuur Ezzatyhusna Mk; Nurul Izzati Hassan; Siti Suraiya MN; Suharni M (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Loop-mediated isothermal amplification (LAMP) is a gene amplification technique whereby the amplification products are commonly visualized as turbidity by naked eye in the presence of magnesium pyrophosphate precipitation. An appropriate intercalating dye is important as it could increase the sensitivity and reduce the false positive and false negative results for the detection. The study aimed to compare the performance of three different intercalating dyes; SYBR Green I, SYBR Safe and calcein-based dyes in HPV-16 LAMP assay by naked-eye visualization, gel electrophoresis and real-time monitoring. The LAMP assay was carried out using a Loopamp DNA amplification kit in 25 μl volumes. The reaction mixture was incubated at 60